Chat-GPT Integration in Task-Based Language Teaching to Improve Opinion, Reasoning, and Information Gaps in English Language Learning to Improve Speaking Skills - Nurapriani, Reni; Darmawan, Deni; Rusman (Jurnal Pendidikan Indonesia, 2025)
This research is motivated by the low speaking skills of early childhood students. The use of conventional learning media is one of the causes necessitating technology adoption. This study aimed to analyze the effect of Chat-GPT integration based on opinion, reasoning, and information gap tasks on speaking skills. This study used a quasi-experimental research method involving 252 early childhood students. The three experimental groups received treatment in the form of the use of Chat-GPT in language teaching based on opinion, reasoning, and information gap tasks. All groups were tested on their initial speaking skills. The experimental group was given an intervention in opinion, reasoning, and information gap tasks, while the control group was given a traditional intervention to improve speaking skills. Data analysis was conducted using one-way ANOVA. The results showed that the experimental group in all three groups showed significant improvements in speaking skills compared to students in the control group in the posttest phase. The implications of this study demonstrate the transformative potential in English learning, especially in speaking skills. Using Chat-GPT as a supporting tool in communication-based task activities allows students to explore various perspectives, strengthen their reasoning skills, and organize information more logically and structured.